The Impact of Project-Based Learning on Students' Engagement and Performance in English-Speaking Class at Senior High School - Resty Wahyuni (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the process of the implementation of speaking using project- based learning method in speaking class at Senior High School and to find out whether the performance of project-based learning in speaking Class, in class twelve Senior High School. The type of research used qualitative method. The implementation of PjBL enables collaboration between students, strengthens social skills, and builds the ability to work in teams. Projects require active communication, sharing of ideas, and assignment of tasks, which can shape students' interpersonal skills. PjBL also provides opportunities for students to develop soft skills, such as leadership, collaboration, and time management, which have long-term value in their personal and professional lives. The result show that the students implementing their project follow the step of the implementing the project during learning in the class. Based on the explaining about we can conclude that the implementing of project-based learning method in speaking class can make the students have to take an active role.